An empirical case study on mathematics preservice teachers' pedagogical content knowledge related to the limit and continuity concepts with regard to students' difficulties* - (:unkn) unknown (Nova Science Publishers, Inc., 2011)
The teacher knowledge of students' understanding of mathematics refers to the knowledge teacher must have about students in order to help them develop specific knowledge. This component of pedagogical content knowledge includes two categories of knowledge: requirements for learning specific mathematics concepts, and areas of mathematics that students find difficult. The second refers to pre-service teachers' knowledge of the mathematical concepts or topics that students have misconceptions, make mistakes and find difficult to learn. Sure, this knowledge plays an important role in teacher preparation to teaching. Therefore the fact that a pre-service teacher uses and interprets students' difficulties in his/her teaching is an important skill to be gained in faculties. In this chapter, we aimed at investigating pre-service teachers' pedagogical content knowledge related to the limit and continuity concepts with regard to students' difficulties. In order to gather data, we conducted multiple research methods such as observation, interviews and document analysis. The main research group of the study is comprised of four last year pre-service teachers from the department of Secondary School Mathematics Teaching. They were selected after the analysis of a content knowledge questionnaire related to the limit and continuity concepts. This questionnaire was administered to 37 pre-service teachers. Firstly, semi-structured interviews were conducted with the four pre-service teachers. Thereafter by giving sufficient time they were asked to prepare a lesson plan concerning the limit and continuity concepts and to lecture it through micro-teaching. One of the main results of the study is that the preservice teachers' knowledge of students' difficulties concerning the limit and continuity concepts was limited and associated to their content knowledge. © 2011 by Nova Science Publishers, Inc. All rights reserved.
Keywords: Knowledge of students' difficulties; Limit and continuity concepts; Pedagogical content knowledge; Teacher training